NEP 2020: INTEGRATED TEACHER EDUCATION PROGRAM AND ITS OPPORTUNITIES AND CHALLENGES - Shivalingappa, Veena; Narayanappa, Venkoba (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the present article, the role of teacher in the national education policy has been discussed in accordance with the new education policy. In accordance with this policy, a lot of expectations have been expressed from the teacher. A position has been taken that teachers should focus on student-centered strategy. Because every student has some inherent talents, they should be discovered, nurtured, encouraged and developed. These talents may manifest as various interests, inclinations or abilities. Students who show special interest and ability in a field should be encouraged to study that field beyond the normal school curriculum. Teacher education will include methods of identifying and stimulating the talents and interests of such students. Such is explained in this policy. This research essay is presented with the intention of highlighting the role of these teachers.